Innovation in Accelerating Diabetic Ulcer Wound Healing Using a Combination of Moist Wound Healing and Modern Dressing Methods Based on Buloh Bee Honey Ointment - Arfah May Syara; Yuni Suharnida Lubis (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
Background: Buloh honey possesses antibacterial and anti-inflammatory properties, as well as the ability to accelerate tissue regeneration. The innovative combination of Moist Wound Healing (MWH) and modern dressing based on Buloh bee honey provides an effective, safe, and affordable solution for managing diabetic foot ulcers. This approach can improve patients’ quality of life and reduce both the economic and public health burdens caused by poorly managed diabetic complications. Objective: To analyze the acceleration of diabetic ulcer wound healing before and after the intervention using the combination of MWH and modern dressing based on Buloh bee honey. Method: This study employed a quasi-experimental research design with a control time series comparison group. Results: Wound healing was assessed using the Bates-Jensen Wound Assessment Tool, which evaluates parameters such as wound size, depth, edge condition, tunneling, necrotic tissue type and area, exudate type and amount, surrounding skin condition, peripheral edema, granulation tissue size, peripheral induration, and epithelialization area. The results showed that the combination of Moist Wound Healing (MWH) and Buloh bee honey ointment accelerated the healing of diabetic ulcers compared to conventional treatment. In the first week, the intervention group began to show healthy granulation tissue formation and reduced exudate, while the control group demonstrated slower improvement. By the fourth week, 73.1% of participants in the intervention group reached near-complete epithelialization, compared to 41.8% in the control group. Conclusion: The combination of MWH and Buloh bee honey ointment proved to be more effective in accelerating diabetic ulcer healing than conventional care. This intervention promotes faster new tissue formation, reduces exudate, and enhances wound epithelialization. The approach is safe, natural, and recommended as an alternative therapy for chronic wounds in diabetic patients.